2021
DOI: 10.1111/dth.15141
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic vasculitis as a cutaneous manifestation of ChAdOx1 nCoV‐19 corona virus vaccine (recombinant)

Abstract: With the present COVID‐19 vaccination drive across the world, adverse skin reactions post COVID‐19 vaccine is expected. Majority of these reactions seen were transient or local injection site reactions. However, as the larger population is being vaccinated, certain uncommon dermatological presentations including leukocytoclastic vasculitis, pityriasis rosea, and exacerbation of pre‐existing autoimmune diseases are now being reported. Among all the COVID‐19 vaccines, most of these reactions are seen with messen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one had cryoglobulinemia. 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine. PCR of a skin swab for varicella‐zoster virus (VZV) resulted positive, and VZV IgM and IgG antibodies were positive.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty cases of COVID‐19‐vaccine triggered‐LCV were noted; three with an elevated anti‐Spike SARS CoV‐2 Antibody titer, two of them had no history of COVID‐19.Oral mucosal involvement was noted in one case. Only one had cryoglobulinemia 7,18–33,36,37 . Nastro et al 21 reported an 84‐year‐old woman, with history of chronic kidney disease and depressive disorder, developed burning pain on the distal part of right leg and foot, followed by ipsilateral multiple non‐confluent purpuric papules and vesicles few hours after she received the first dose of Pfizer‐BioNTech COVID‐19 vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…Three of five erythema multiforme cases were associated with the mRNA-1273 vaccine [ 1 , 62 , 63 ]. New onset of prurigo nodularis [ 17 ], radiation recall dermatitis [ 64 ], symmetrical drug-related intertriginous and flexural exanthema (SDRIFE)-like eruption [ 65 ], Stevens-Johnson syndrome/toxic epidermal necrolysis [ 66 , 67 , 68 ], Sweet’s syndrome [ 69 , 70 ], vitiligo [ 71 ], vasculitis [ 50 , 72 , 73 ], livedo racemosa [ 27 ], fixed drug eruption [ 27 ], pityriasis rubra pilaris-like eruption [ 74 ], and facial pustular neutrophilic eruption [ 75 ] have been reported post-vaccination. All SJS and Sweet’s syndrome cases were managed successfully.…”
Section: Resultsmentioning
confidence: 99%
“…The exact pathogenesis of vaccination-associated leukocytoclastic vasculitis has yet to be determined, but SARS-CoV-2 vaccine might result in the activation of autoreactive B/T cells, antibody formation, and immune complex deposition within small vessels, leading to activation of the complement system and recruitment of leukocytes [ 4 , 6 , 7 , 9 , 10 ]. The responsible particle as an antigen for such reactions is unknown, however inflammatory response to vaccine component encoding SARS‐CoV‐2 spike glycoprotein, targeting endothelium and resulting in small-vessel vasculitis, could be hypothesized [ [11] , [12] , [13] ].…”
Section: Discussionmentioning
confidence: 99%